The Relationship of Os. Femur with Height influenced by Gender, Race, and Nutrition for Medical Student In Faculty of Medicine University Wijaya Kusuma Surabaya - Soekanto, Ayly; Sani, Imamir Mudzadadil Alfi (Universitas Muhammadiyah Sumatera Utara, 2023)
Height is an important identity in forensics. Several long bones are known to be used for size estimation, one of which is the femur (Os. Femur). Personal height growth is affected by many factors, including gender, breed, and diet. This study aimed to analyze the correlation of Os length. Thigh height in UWKS medical students is influenced by gender, ethnicity and diet. This study used an observational descriptive analysis approach to conduct a cross-sectional study. Forty-four students from the UWKS School of Medicine participated in the study. Height measurement using Microcotoise, Os. Femoral New Deland with sliding calipers and weights with scales. Data were analyzed using normality test, Pearson correlation test, and simple linear regression test. The results show that there is a positive and very strong correlation between the Os lengths. Femur size, non-Javanese ethnicity, and normal, obese, and obese dietary categories in a male sample. There is now a strong positive relationship between femur length and height in the female sample. Meanwhile, the Os length has no correlation. Keywords: length os femur, height, gender, ethnicity, nutrition